Efficacy of Paecilomyces lilacinus (Thorn.) Samson in suppressing nematode infestations in black pepper (Piper nigrum L.) - RAMANA, K V (Journal of Spices and Aromatic Crops, 1994)
The efficacy of Paecilamyces lilacinus in snppressing root-knot nematode (Melaidogyne incognita) and bnrrowing nematode (Radapholus similis) infestations in black pepper (Piper nigrum) was studied. Though the fungus could not effect absolute control of nematodes, it signficantly suppressed nematode infestation and increased total root mass production. The fungus was more effective in suppressing M. incognita than R. similis.